Energy savings of the actuators operation on the enterprises for repair of railway equipment - Marenych, O. O. (Science and Transport Progress, 2008)
In this article the following problem has been considered: ways of efficiency increase for electric drives installed at the railway machinery repair enterprises taking into account the specific conditions of technological processes.